CAPITAL PUNISHMENT FOR BLASPHEMY IN THE HADITH OF THE PROPHET: A Perspective through the Common Link Theory - Akbar, Irwan Ahmad; Roibin, Roibin (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
This study aims to investigate the authenticity of the hadith that permits the death penalty for those who insult the Prophet. Through the lens of the Common Link theory, the research seeks to examine this hadith by applying isnad criticism. The study employs a qualitative methodology, using a library research approach to analyze and understand the relevant hadiths. Data is collected from various primary hadith collections, which are then analyzed through contextual review and source criticism and compared with the commentaries of hadith scholars and relevant academic literature. The objective of this research is to determine whether the hadith in question is valid as a basis for justifying the death penalty for blasphemy against the Prophet. Ultimately, the findings of this study conclude that the hadith falls into the category of gharib nisbi. Furthermore, ‘Utsman al-Syaham is identified as a fabricator of this hadith. Regarding his reliability, al-Syaham is a controversial figure whose credibility is debated among scholars and hadith critics. Consequently, this hadith is deemed insufficient to be used as a legitimate basis for implementing the death penalty for insulting the Prophet.[Penelitian ini berupaya untuk menelusuri otentitisitas hadits mengenai kebolehan menghukum mati penghina Nabi. Melalui lensa teori Common Link. Penelitian ini berusaha memeriksa hadis tersebut dengan kritik isnad. Penelitian ini menggunakan metodologi kualitatif dengan pendekatan library research untuk menganalisis dan memahami hadis-hadis terkait. Data dikumpulkan dari berbagai kitab hadis primer, kemudian dianalisis melalui tinjauan kontekstual dan kritik sumber, serta dibandingkan dengan komentar para ulama dan literatur akademis yang relevan. Penelitian ini bertujuan untuk mengetahui apakah hadis tersebut layak digunakan sebagai dasar untuk membenarkan tindakan hukum mati bagi penghina Nabi. Pada akhirnya, hasil penelitian ini menyimpulkan bahwa hadits ini tergolong ke dalam gharib nisbi. Adapun ‘Utsman al-Syaham adalah fabrikator hadits. Dari aspek ketsiqahan, al-Syaham tergolong ke dalam sosok yang diperdebatkan kekredibelannya di tengah para ulama dan kritikus hadits. Oleh karena itu, hadits ini tidak cukup untuk dapat dijadikan hujjah dalam menghukum mati penghina Nabi.]